Facile hydrolysis synthesis of Bi4O5Br2 photocatalyst with excellent visible light photocatalytic performance for the degradation of resorcinol. Issue 53 (13th May 2016) - Li, Min; Cui, Yujin; Jin, Yongsheng; Li, Hui
Abstract : A Bi4 O5 Br2 photocatalyst had been synthesized successfully through a facile, one-step, and energy-saving hydrolysis route. Abstract : A Bi4 O5 Br2 photocatalyst had been synthesized successfully through a facile, one-step, and energy-saving hydrolysis route. The crystal structure, morphology, composition, optical property, and specific surface area of the as-synthesized material were characterized by X-ray diffraction, scanning electron microscopy, high-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, UV-vis diffuse reflection spectra and N2 adsorption–desorption isotherms, respectively. Moreover, the photocatalytic activity of Bi4 O5 Br2 for resorcinol degradation under visible light irradiation was investigated systematically. The results revealed that the as-prepared Bi4 O5 Br2 photocatalyst exhibited strong visible light absorption (band gap energy 2.0 eV), and large specific surface area (62.25 m 2 g −1 ), which resulted in the enhanced photocatalytic performance for resorcinol degradation. Compared with BiOBr and P25, the photocatalytic activity of Bi4 O5 Br2 was appropriately 31 and 12 times higher, respectively. The active oxygen species of h +, ˙OH, and ˙O2 − dominated the resorcinol degradation process over the Bi4 O5 Br2 photocatalyst. In addition, the relatively high stability of Bi4 O5 Br2 will benefit its practical application for the treatment of other organic pollutants.